2011
DOI: 10.1373/clinchem.2010.159830
|View full text |Cite
|
Sign up to set email alerts
|

Outliers as a Cause of False Cardiac Troponin Results: Investigating the Robustness of 4 Contemporary Assays

Abstract: BACKGROUND:It is important that cardiac troponin be measured accurately with a robust method to limit false results with potentially adverse clinical outcomes. In this study, we characterized the robustness of 4 analytical platforms by measuring the outlier rate between duplicate results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 15 publications
4
52
3
Order By: Relevance
“…The patients with cTnT outliers had significantly lower renal function than those patients with cTnI outliers, and this may have contributed to their identification as outliers. Despite the obvious differences in the underlying mechanisms the between-method outliers occurred with approximately the same rate on cTnI platforms as the within-method outliers detected by duplicate analysis of samples (betweenmethod outlier rate per patient vs within-method outlier rate per sample: Abbott 0.06% vs 0.10%; Beckman Coulter 0.28% vs 0.44%; Siemens 0.11% vs 0.10%) (6,17 ). The outlier rate between methods of 0.68% with the Roche cTnT assay was higher than the 0.06% within-method outlier rate.…”
Section: Fig 2 Difference Plots Illustrating the Observed And Withimentioning
confidence: 85%
See 2 more Smart Citations
“…The patients with cTnT outliers had significantly lower renal function than those patients with cTnI outliers, and this may have contributed to their identification as outliers. Despite the obvious differences in the underlying mechanisms the between-method outliers occurred with approximately the same rate on cTnI platforms as the within-method outliers detected by duplicate analysis of samples (betweenmethod outlier rate per patient vs within-method outlier rate per sample: Abbott 0.06% vs 0.10%; Beckman Coulter 0.28% vs 0.44%; Siemens 0.11% vs 0.10%) (6,17 ). The outlier rate between methods of 0.68% with the Roche cTnT assay was higher than the 0.06% within-method outlier rate.…”
Section: Fig 2 Difference Plots Illustrating the Observed And Withimentioning
confidence: 85%
“…The study population, quality control procedures, imprecision parameters, and identification of withinmethod outliers have been described in detail (6 ). Serum cardiac troponin was measured on 4 contemporary analytical platforms: (a) Abbott Architect i2000SR analytical system with STAT Troponin-I reagent (Abbott Diagnostics); (b) Beckman Coulter Access2 analyzer with Enhanced AccuTnI reagent (reagent part no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturer's LoB and LoD data were used for the Roche cTnT assay owing to the absence of a suitable sample diluent. We checked for random outliers in the Beckman Coulter cTnI assay with analysis of duplicates (9 ).…”
Section: Statistical Proceduresmentioning
confidence: 99%
“…4 Another study using a contemporary cTnI assay from the same manufacturer in serum samples had an overall outlier rate of 0.21% (5/2391) (and singlet measurement outlier rate of 0.10%) but the duplicates were performed on a single instrument as a daily batch analysis. 5 Our study only evaluated for outliers in samples with elevated cTnI values (up to 300 ng/L) as previous studies have shown that the vast majority of cTn outliers give a falsely higher result [3][4][5] (thus normal results were excluded) and using a contemporary Abbott cTnI assay the majority (91.1-96.4%) of outliers occur at 4260 ng/L. 4 The outlier rates in our study, therefore, cannot be directly compared with the overall outlier rates reported in other studies.…”
Section: Discussionmentioning
confidence: 99%